Improvement Of Winemaking Technology on The Basis of The Study of Antioxidant Activities (Texas Journal of Agriculture and Biological Sciences, 2023)
On a global scale, in the perspective of the development of the wine industry, it is planned to increase the production of aged vintage dry and high-quality fortified wines that meet modern market requirements. The main directions of development of the national economy of Uzbekistan provide for the expansion of the range and improvement of the quality of food products, including wine-making. The action strategy for the further development of the Republic of Uzbekistan defines the tasks for “further modernization and diversification of industry by transferring it to a qualitatively new level, aimed at advancing the development of high-tech manufacturing industries, primarily for the production of finished products with high added value based on the deep processing of local raw materials